Effects of a preventive behaviors development program for Diabetes Mellitus risk at Kut Chum District, Yasothon Province - sangsri, aree; Iemsawasdikul, Warinee; Potisupsuk, Chuenjit (Thai Journal of Nursing, 2021)
The objectives of this quasi-experimental research were to compare preventive behaviors and blood sugar of experimental group before and after experiment, and after experiment between experimental group and comparison group. The sample comprised 62 Diabetes Mellitus risks, who had fasting blood sugar for 8 hours 120-125 mg./dl. but not diagnosed DM by doctor, aged 35-60 yrs, lived in responsible area of Nonpuoy Tambon Health Promoting Hospital and Nongkae Tambon Health Promoting Hospital, Kut Chum District, Yasothon Province. They were selected by purposive sampling technique and equally devided into experimental group and comparative group using the matched-pairs method. The experimental tools were: 1) Preventive Behaviors Development Program for Diabetes Mellitus risk based on health belief model of Becker; 2) questionnaires with 2 parts: (1) general data, and (2) preventive behaviors (CVI 0.74, and reliability 0.98); and 3) glucometer. Data were analyzed by descriptive statistics, t-test, and Wilcoxon signed-rank test . The results found as follows. After the experiment, preventive behaviors and exercise behaviors of the experimental group were significantly higher than before experiment and that of the comparative group; eating behaviors of the experimental group were significantly higher than before experiment and increased more than the comparative group (p < .05). After the experiment, fasting blood sugar of the experimental group was significantly lower than before experiment and the comparative group (p < .05).